From one Orient to multiple Orients: novelties at east of Rome - Romano, Antonella (Cuadernos de Historia Moderna, 2023)
In the 16th century, Rome experienced a long-term transformation in its knowledge and redefinition of the "Orient". This experience took place at the crossroads of multiple forms of knowledge and practices, both learned and ordinary, which redefined the links between Antiquity and the contemporary world. This article proposes to highlight the re-articulation of the space-time references of the Urbs, a privileged space for a confrontation between Egypt, constructed as the pivot of the ancient Orient, and Japan, the expression of the modern extreme Orient. This comparison opens up a new understanding of the knowledge production in the papal capital.
Keywords: Orient; Japan; Egypt; philology; hieroglyphs; obelisks; maps; knowledge